Current Global Trends in Prepectoral Breast Reconstruction - Saima Taj; Ravi Chandavarkar; Raghavan Vidya (Medicina, 2024)
Implant-based breast reconstruction (IBBR) is the most frequently performed procedure for breast reconstruction following mastectomy, which involves the surgical placement of breast implants. The approach to breast reconstruction can be divided into two main categories, namely prepectoral breast reconstruction (PPBR) and subpectoral breast reconstruction (SPBR), based on the implant plan and placement technique. In recent years, there has been a significant surge in the popularity of prepectoral implant-based breast reconstruction, where the implants are positioned above the chest muscle, as opposed to beneath it in the subpectoral approach. However, despite this growing preference, there is a lack of comprehensive data regarding the national trends in the utilization of this technique, thus necessitating further investigation. This narrative review aims to ascertain the current global patterns linked to prepectoral breast reconstruction and elucidate the considerations surrounding patient and implant selection, reconstructive techniques, the utilization of meshes in prepectoral reconstruction, the ensuing outcomes and complications, the ramifications of radiotherapy, and the potential advantages of integrating fat infiltration into the implementation of this technique in breast reconstruction with a focus on published papers in last five years. Conclusion: Prepectoral breast reconstruction has emerged as an appropriate surgical option for individuals seeking breast reconstruction. This development can be attributed to the recent progress made in implant technology, which has significantly enhanced the outcomes of this procedure. Additionally, advancements in mastectomy techniques, autologous fat grafting, and the use of acellular dermal matrices (ADMs) have also played a vital role in improving the aesthetic results of prepectoral breast reconstruction. As a result, the significance and effectiveness of this technique in the field of breast reconstruction have been firmly established, making it an essential component of the overall armamentarium available to plastic surgeons for breast reconstruction purposes.